Elucidation of the Chemopreventive Role of Stigmasterol Against Jab1 in Gall Bladder Carcinoma - Pandey, Pratibha; Bajpai, Preeti; Siddiqui, Mohammad H.; Sayyed, Uzma; Tiwari, Rohit; Shekh, Rafia; Mishra, Kumudesh; Kapoor, V.K. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Plant sterols have proven a potent anti-proliferative and apoptosis inducing agent against several carcinomas including breast and prostate cancers. Jab1 has been reported to be involved in the progression of numerous carcinomas. However, antiproliferative effects of sterols against Jab1 in gall bladder cancer have not been explored yet. Objective: In the current study, we elucidated the mechanism of action of stigmasterol regarding apoptosis induction mediated via downregulation of Jab1 protein in human gall bladder cancer cells. Methods: In our study, we performed MTT and Trypan blue assay to assess the effect of stigmasterol on cell proliferation. In addition, RT-PCR and western blotting were performed to identify the effect of stigmasterol on Jab1 and p27 expression in human gall bladder cancer cells. We further performed cell cycle, Caspase-3, Hoechst and FITC-Annexin V analysis, to confirm the apoptosis induction in stigmasterol treated human gall bladder cancer cells. Results: Our results clearly indicated that stigmasterol has up-regulated the p27 expression and down-regulated Jab1 gene. These modulations of genes might occur via mitochondrial apoptosis signaling pathway. Caspase-3 gets activated with the apoptotic induction. Increase in apoptotic cells and DNA were confirmed through annexin V staining, Hoechst staining, and cell cycle analysis. Conclusion: Thus, these results strongly suggest that stigmasterol has the potential to be considered as an anticancerous therapeutic agent against Jab1 in gall bladder cancer.
Keywords: therapeutics